(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يناقش البحث واقع القطاع الزراعي في سورية، ودراسة أهم الخصائص التي يمتاز بها والمشاكل التي يعاني منها، ويحاول الباحث من خلال دراسة تحليلية لواقع الزراعة في سورية استبيان طرق، وأساليب التسويق الزراعي في سورية، وآليات التسعير، وبالتالي يتضمن دراسة الخصائص العامة للزراعة السورية من خلال تحديد المشكلات التي تشكل عائقاً أمام تطور القطاع الزراعي من ناحية الأرض، والعمل، ورأس المال، والتنظيم، ودراسة وصفيّة لتطور الإنتاج الزراعي في سورية، وتحليل أساليب تسويق المنتجات الزراعية من خلال دراسة قطاعات التسويق، ووصف واقع تسعير المنتجات الزراعية وأسس تحديد الأسعار في القطر العربي السوري في إطار الخطة العامة للدولة. The research discusses the reality of the agricultural sector in Syria and examines its most important advantages along with the problems affecting them. The researcher attempts through an analysis of the reality of Agriculture in Syria to examine the ways and means of agricultural marketing and pricing mechanisms; consequently, he studies the characteristics of the Syrian agriculture through the identification of problems which act as impediments to the development of the agricultural sector in terms of land, labor, capital, management. The research also includes a descriptive study of the evolution of agricultural production in Syria, and an analysis of the marketing of agricultural products through the marketing sectors, describing the reality of the pricing of agricultural products and the foundations for fixing prices in the Syrian Arab Republic in the framework of the general plan State.